Evolution, Expression, and Function of Nonneuronal Ligand-Gated Chloride Channels in Drosophila melanogaster. Issue 7 (1st July 2016) - Remnant, Emily J; Williams, Adam; Lumb, Chris; Yang, Ying Ting; Chan, Janice; Duchêne, Sebastian; Daborn, Phillip J; Batterham, Philip; Perry, Trent
Abstract: Ligand-gated chloride channels have established roles in inhibitory neurotransmission in the nervous systems of vertebrates and invertebrates. Paradoxically, expression databases in Drosophila melanogaster have revealed that three uncharacterized ligand-gated chloride channel subunits, CG7589, CG6927, and CG11340, are highly expressed in nonneuronal tissues. Furthermore, subunit copy number varies between insects, with some orders containing one ortholog, whereas other lineages exhibit copy number increases. Here, we show that the Dipteran lineage has undergone two gene duplications followed by expression-based functional differentiation. We used promoter-GFP expression analysis, RNA-sequencing, and in situ hybridization to examine cell type and tissue-specific localization of the three D. melanogaster subunits. CG6927 is expressed in the nurse cells of the ovaries. CG7589 is expressed in multiple tissues including the salivary gland, ejaculatory duct, malpighian tubules, and early midgut. CG11340 is found in malpighian tubules and the copper cell region of the midgut. Overexpression of CG11340 increased sensitivity to dietary copper, and RNAi and ends-out knockout of CG11340 resulted in copper tolerance, providing evidence for a specific nonneuronal role for this subunit in D. melanogaster . Ligand-gated chloride channels are important insecticide targets and here we highlight copy number and functional divergence in insect lineages, raising the potential that order-specific receptors could be isolated within an effective class of insecticide targets.